A community based approach to bicycle helmet use counts. Issue 4 (December 1996) - Becker, L. R.; Mandell, M. B.; Wood, K.; Schmidt, E. R.; O'Hara, F.
Abstract : OBJECTIVE: Bicycle helmet use has become an important measure of the effectiveness of bicycle safety programs and the effectiveness of helmet legislation. Accounts of analytical comparisons of observation site selection methods are scarce. This report addresses this gap by reporting the relative effectiveness and costs of two alternative approaches to the selection of observation sites for helmet use counts. METHODS: The community based (COBA) method of site selection entailed asking community informants to identify locations frequented by young bicycle riders. In the bicycle club/map (CLMA) method, site selections were based on recommendations from club members of sites at which cyclists were likely to be found and through examination of maps, keying on local features. These alternative site selection methods were compared in terms of their overall and cost effectiveness in locating youth riders. RESULTS: Despite fewer observer hours and fewer sites in a sparsely populated rural county, the COBA method yielded greater numbers of riding youth and from 1.9 to 4.6 times more youth riders per observer hour than did the CLMA method in two densely populated suburban counties. In addition, costs per youth rider observed associated with the COBA method were 2.9 to 7.0 times lower than those associated with the CLMA method. CONCLUSIONS: Community based site identification is both more efficient in locating youth riders and more cost effective.